2019
DOI: 10.5812/compreped.84274
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition in Children with Congenital Heart Disease

Abstract: Background: Congenital heart defect (CHD) is the most common congenital anomaly in infants and is known to be a leading cause of malnutrition. Objectives: This study aimed to provide insights into the prevalence of malnutrition in children with CHD in Iran. Methods: The study enrolled 515 under-five children with CHD. The diagnosis was based on the definitive result of cardiac catheterization report. They were divided into the subgroups of cyanotic with pulmonary hypertension (PH), acyanotic with PH, cyanotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
4
7
1
Order By: Relevance
“…Likewise, height below 5 th percentile was much more common in cyanotic CHD in comparison with acyanotic CHD (65.6% vs 9.1%). Similar findings were reported by Tabib et al and Ulfa et al 26,27 Other growth parameters analysed in our study such as weight for age and height for age measured also significantly lower in cyanotic groups of CHD. Noticeably, results of our analysis showed that cyanotic CHD group had significantly longer cardiopulmonary bypass (CPB) time, aortic cross-clamp (ACC) time and longer intensive care unit length of stay.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, height below 5 th percentile was much more common in cyanotic CHD in comparison with acyanotic CHD (65.6% vs 9.1%). Similar findings were reported by Tabib et al and Ulfa et al 26,27 Other growth parameters analysed in our study such as weight for age and height for age measured also significantly lower in cyanotic groups of CHD. Noticeably, results of our analysis showed that cyanotic CHD group had significantly longer cardiopulmonary bypass (CPB) time, aortic cross-clamp (ACC) time and longer intensive care unit length of stay.…”
Section: Discussionsupporting
confidence: 92%
“…This difference could be due to the age of inclusion, settings and capacity of the institutions and design differences ( 17 , 18 ). Our report is higher than reports from Uganda(31.5%) and Iran (39.8%)( 15 , 19 ). The higher figure in our study could be a reflection of the high national burden of malnutrition in Ethiopia( 5 ).…”
Section: Discussioncontrasting
confidence: 88%
“…Malnutrition in CHD patients can be categorized into different groups depending on the presence or absence of cyanosis/pulmonary hypertension/heart failure. Several combinations including acyanotic patients with pulmonary hypertension (patients with left-to-right shunt and pulmonary hypertension),acyanotic patients without pulmonary hypertension and cyanotic patients are used (4,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cyanotic or acyanotic CHD without pulmonary hypertension had higher body weight and body height rates compared to CHD with pulmonary hypertension. 34 We found a significant relationship between time period after PDA closure and nutritional status, before and 1, 3, 6, and 12 months post-closure. A Yogyakarta study also showed that body weight significantly increased after transcatheter PDA closure.…”
Section: Resultsmentioning
confidence: 56%
“…33 Malnutrition in PDA may induce failure to thrive, as well as developmental and cognitive disorders. 34 In Yogyakarta, malnutrition was noted in 76.7% of patients diagnosed with PDA. 14 Similarly, 80% of our patients had malnutrition, including 40% with severe malnutrition prior to transcatheterization.…”
Section: Resultsmentioning
confidence: 99%